(untitled) (International conference on multidisciplinary science, 2024)
caries disease - among mankind is the most common disease, occurring in 93% of people. Caries is derived from the Latin word rot. Caries is a complex, slow-moving pathological process in its hard tissues as a result of damage to tooth enamel, caused by bacteria of the oral cavity, mainly Streptococcus mutans and Streptococcus sanguis. In general, caries disease in young children is caused by improper oral hygiene, irregular and ineffective cleaning of teeth, irrational diet, eating a lot of food rich in soft carbohydrates, low consumption of raw fruits, hypovitaminosis, lack of certain minerals (fluorine, phosphorus, calcium) in drinking water, at a young age. As a result of rickets, tuberculosis, improper formation of teeth, weakened immunity and pathology of the gastrointestinal system are considered to be one of the urgent problems of medicine today.